Perancangan mesin pengupas dan pemotong bawang merah - Mohammad Habib Al hidayat (UNIVERSITAS ISLAM MALANG, 2019)
This onion peeler and cutter machine is one of the aims to support the increase in the production of stripping and slicing onions, the onion peeler and cutter machine are efficient and effective in peeling and cutting shallots which are ready to be fried or cooked as needed. the onion peeler and cutter machine uses electric motor power and the price is relatively cheap, so it can be done in villages especially in home industries.the purpose and objective of this research is to study the design of the onion peeler and slice so that it is hoped that the onion extractor and cutter can be produced by not requiring long time to peel and cut the shallots. a driving force of 0.5 HP is needed to produce the results of peeling and cutting onion as needed.geometry considerations include machines having diameters ranging from 600 MM, and height 1,100 MM. frame construction uses the L profile to facilitate the arrangement and construction. the transmission shaft uses S30C carbon steel with a strong tensile strength of 48 kg / mm2 to be used as a transmission shaft, besides that the S30C carbon steel is relatively cheap compared to other carbon steels. knife for peeler and cutter onion using mild steel with tensile strength 37 kg / mm2, so the sharpness of the knife is maintained.